Combustion and emission control strategies for partially-premixed charge compression ignition engines: A review. (15th February 2022) - Bobi, Shahzad; Kashif, Muhammad; Laoonual, Yossapong
Graphical abstract: Highlights: PCCI offers low-temperature combustion to reduce NOx and soot emissions. Advanced injection timing and high injection pressure provide better fuel atomization and vaporization. A high percentage of EGR and low compression ratio are the sources of the dilute air-fuel mixture. Intake air temperature of 70 –80 °C and ON of 70–87 are moresuitable for PCCI mode. Advanced narrow angle injection and suitable compression reduce HC and CO emissions.. Abstract: Partially premixed charge compression ignition (PCCI) engine presents superior fuel economy and ultra-low NO x and particle matter emissions compared with the conventional combustion engine. The benefits of low emission of SI engine and higher thermal efficiencies of diesel engine are combined to meet the stringent emission regulations and carbon dioxide emissions reduction goals by employing advanced modes of combustion like Gasoline compression ignition, Homogeneous Charge Compression Ignition (HCCI) etc. Yet issues such as relatively high HC and CO emissions remain unsolved at certain operating conditions. Therefore, the objective of this paper is to provide an inclusive review of the effects of intake strategies on the combustion characteristics, reliability and emissions of PCCI engines with fossil and alternative fuels. Several intake strategies and parameters viz., advance injection timing, injection pressure, exhaust gas recirculation (EGR) fraction, type and quality of fuel, engine compression ratio, and intake air temperature, have been discussed, and their effects on the performance of PCCI engine has been analyzed based on the published studies reporting experimental results. The aforementioned techniques and controlling strategies can be used alone or in combination to control the in-cylinder temperature, pressure, and mixture distribution in the cylinder at the end of the compression stroke. This in turn will allow the charge mixture to auto-ignite at the desired crank angle resulting in optimal combustion phasing and heat release rate over a wide operating range. Thus, this paper thoroughly reviews and summarizes various effective techniques and controlling strategies used in the PCCI engine. This can help meet stringent emission regulations on vehicles and can help meet the carbon dioxide reduction goal in the short and medium term.